Analisis Potensi Bisnis Online Syariah pada Peningkatan Pendapatan Penjualan Sirup Jeruk Kalamansi melalui E-Commerce - Kurniawan, Adhadi (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2019)
This study describes the potential of sharia online business on increasing the income of the company through e-commerce. This research method is a qualitative descriptive approach. Data collection techniques such as observation, documentation and interviews. The results of this study indicate that in online marketing, the business of selling kalamsi liebhy itself goes through the stages as follows: 1. Creating the concept of displaying Liebhy Kalamansi product photos; 2. Displaying Photos of Goods in Realpict; 3. Providing services to prospective customers by establishing two-way communication so that prospective customers decide to close and make payments and direct the Bai ’Assalam contract; 4. A neat packing process and keep the goods sent from being damaged during delivery until it reaches the customer's hands. Some summaries of the results of interviews conducted show sales through e-commerce conducted by liebhy kalamansi on shoppe and instagram. This certainly provides financial benefits to the liebhy kalamansi in an effort to expand sales in a wider market.Keywords: Sharia Online Business, E-Commerce, Kalamansi